Effect of circulating immune complexes on the binding of rheumatoid factor to histones - Gussin, H. (2000)
OBJECTIVE—To determine whether the reaction of rheumatoid factor (RF) with solid phase histone is due to the simultaneous presence of circulating immune complexes (CICs) or aggregated IgG. METHODS—Serum samples from 56 patients with seropositive rheumatoid arthritis (RA) and 50 random blood bank donors were used. Binding of immunoglobulins to histone was determined by enzyme linked immunosorbent assay (ELISA) and by western blots. Aggregated IgG was obtained by heating at 61(o)C for 30( )minutes. RESULTS—Among the RA sera tested by ELISA, 54% were positive for histone binding by IgM, IgG, or IgA and 20% by IgM only. Heating of normal sera caused a significant enhancement in the binding of IgG to histone (p<0.001). This binding had a non-cognate behaviour—that is, it was destroyed by pepsin treatment of serum and was not significantly inhibited by competition with free histone. The same behaviour was seen for IgM, IgG, and IgA binding from RA sera. However, cognate IgG antibody binding to histone was inhibited by free histone and was resistant to pepsin digestion. Addition of heat aggregated IgG to RA sera or pretreatment of histone with aggregated IgG caused a significant increase in IgM binding to histone. CONCLUSION—IgM, IgG, and IgA RF bind to solid phase histone as a result of attachment to histone of immune complexes or aggregated IgG and not as a result of a cognate reaction with histone.